Isolation and Characterization of Two Chalcone Derivatives with Anti-Hepatitis B Virus Activity from the Endemic Socotraen Dracaena cinnabari (Dragon’s Blood Tree) - Ramzi A. Mothana; Ahmed H. Arbab; Ali A. ElGamal; Mohammad K. Parvez; Mohammed S. Al-Dosari (Molecules, 2022)
Hepatitis B virus (HBV) infection is prevalent and continues to be a global health concern. In this study, we determined the anti-hepatitis B virus (HBV) potential of the Socotra-endemic medicinal plant Dracaena cinnabari and isolated and characterized the responsible constituents. A bioassay-guided fractionation using different chromatographic techniques of the methanolic extract of D. cinnabari led to the isolation of two chalcone derivatives. Using a variety of spectroscopic techniques, including 1H-, 13C-, and 2D-NMR, these derivatives were identified as 2,4’-dihydroxy-4-methoxydihydrochalcone (compound 1) and 2,4’-dihydroxy-4-methoxyhydrochalcone (compound 2). Both compounds were isolated for the first time from the red resin (dragon’s blood) of D. cinnabari. The compounds were first evaluated for cytotoxicity on HepG2.2.15 cells and 50% cytotoxicity concentration (CC50) values were determined. They were then evaluated for anti-HBV activity against HepG2.2.15 cells by assessing the suppression of HBsAg and HBeAg production in the culture supernatants and their half maximum inhibitory concentration (IC50) and therapeutic index (TI) values were determined. Compounds 1 and 2 indicated inhibition of HBsAg production in a dose- and time-dependent manner with IC50 values of 20.56 and 6.36 μg/mL, respectively.